Determinants of arterial elastic function in middle-aged and elderly people: A population-based cross-sectional study from a low-income population in China - Sun, Jiayi; Zhang, Zhen; Fei, Yunhan; Gao, Yannan; Li, Zejian; Gao, Shuai; Wang, Yunfan; Liu, Jie; Tu, Jun; Wang, Haiying; Wang, Jinghua; Ning, Xianjia; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Arterial stiffness is closely associated with the occurrence of many cardiovascular and cerebrovascular diseases. However, the risk factors and mechanisms related to arterial stiffness development have only been partially elucidated. We aimed to describe arterial elastic function and its influencing factors in middle-aged and elderly people in rural China. Methods: This was a cross-sectional study conducted among residents, aged ≥ 45 years, of Tianjin, China, between April and July 2015. Data regarding participant demographics, medical history, lifestyle, and physical examination results were collected and assessed the association with arterial elastic function using linear regression. Results: Of the 3519 participants, 1457 were male (41.4%). Brachial artery distensibility (BAD) decreased by 0.5 %/mmHg with every 10-year increment in age. The mean BAD value was 0.864 %/mmHg lower in women than in men. With each unit increase in mean arterial pressure, the BAD decreased by 0.042 %/mmHg. In patients with hypertension or diabetes, the BAD decreased by 0.726 and 0.183 %/mmHg, respectively, compared with those without hypertension or diabetes. For each unit increase in triglyceride (TG) level, the mean BAD increased by 0.043 %/mmHg. With each increase in body mass index (BMI) category, the BAD increased by 0.113 %/mmHg. Brachial artery compliance (BAC) decreased by 0.007 mL/mmHg with each 10-year increase in age, and brachial artery resistance (BAR) increased by 30.237 dyn·s-1·cm-5. The mean BAC in women was 0.036 mL/mmHg lower and the mean BAR was 155.231 dyn·s-1·cm-5 higher in women than in men. In individuals with hypertension, the mean BAC decreased by 0.009 mL/mmHg and the mean BAR increased by 26.169 dyn·s-1·cm-5. With each increase in BMI category, the mean BAC increased by 0.005 mL/mmHg and the mean BAR decreased by 31.345 dyn·s-1·cm-5. For each unit increase in TG level, the mean BAC increased by 0.001 mL/mmHg. Conclusion: These findings indicate that age, sex, mean arterial pressure, BMI, diabetes, hypertension, and TG level are independently associated with the components of peripheral arterial elasticity. Understanding the factors influencing arterial stiffness is important for developing interventions to minimize arterial aging and cardiovascular and cerebrovascular diseases caused by arterial aging.